(untitled) (Cadernos de Linguagem e Sociedade, 2010)
CHRISTIE, F. & MARTIN, J. R. (EDS.) GENRE AND INSTITUTIONS: SOCIAL PROCESSES IN THE WORKPLACE AND SCHOOL. LONDRES E NOVA YORK: CONTINUUM, 1997, 270 PÁGS.